Specificity of overcoming behavior within relationship to tolerance to uncertainty of convicted men - A. A. Shylina; O. M. Skliarov (Law and Safety)
It has been noted that a person during the execution of a sentence encounters other ways of life, culture, customs and attitudes towards him. Important psychological mechanisms that allow a convicted person to survive in difficult social conditions, to adapt to imprisonment, are strategies of overcoming behavior and tolerance to uncertainty. Tolerance to uncertainty allows the convicts to overcome easily the tension that arises in connection with expectations of constant novelty and changes.